Inhibition of EGF Uptake by Nephrotoxic Antisense Drugs In Vitro and Implications for Preclinical Safety Profiling - Annie Moisan; Marcel Gubler; Jitao David Zhang; Yann Tessier; Kamille Dumong Erichsen; Sabine Sewing; Régine Gérard; Blandine Avignon; Sylwia Huber; Fethallah Benmansour; Xing Chen; Roberto Villaseñor; et al. (Elsevier, 2017)
Antisense oligonucleotide (AON) therapeutics offer new avenues to pursue clinically relevant targets inaccessible with other technologies. Advances in improving AON affinity and stability by incorporation of high affinity nucleotides, such as locked nucleic acids (LNA), have sometimes been stifled by safety liabilities related to their accumulation in the kidney tubule. In an attempt to predict and understand the mechanisms of LNA-AON-induced renal tubular toxicity, we established human cell models that recapitulate in vivo behavior of pre-clinically and clinically unfavorable LNA-AON drug candidates. We identified elevation of extracellular epidermal growth factor (EGF) as a robust and sensitive in vitro biomarker of LNA-AON-induced cytotoxicity in human kidney tubule epithelial cells. We report the time-dependent negative regulation of EGF uptake and EGF receptor (EGFR) signaling by toxic but not innocuous LNA-AONs and revealed the importance of EGFR signaling in LNA-AON-mediated decrease in cellular activity. The robust EGF-based in vitro safety profiling of LNA-AON drug candidates presented here, together with a better understanding of the underlying molecular mechanisms, constitutes a significant step toward developing safer antisense therapeutics. Keywords: kidney, nephrotoxicity, EGF, EGFR, PTEC, antisense, oligonucleotide, safety, preclinical